Targeting cancer homing into the lymph node with a novel anti-CCR7 therapeutic antibody: the paradigm of CLL - Carlos Cuesta-Mateos; Raquel Juárez-Sánchez; Tamara Mateu-Albero; Javier Loscertales; Wim Mol; Fernando Terrón; Cecilia Muñoz-Calleja (Taylor & Francis Group, 2021)
Lymph node (LN) is a key tissue in the pathophysiology of mature blood cancers, especially for chronic lymphocytic leukemia (CLL). Within the multiple de-regulated pathways affecting CLL homeostasis, the CC-chemokine receptor 7 (CCR7) grants homing of CLL cells into the LN where protective environments foster tumor progression. To cover the lack of specific therapies targeting the CCR7-dependence of CLL to enter into the LN, and aiming to displace the disease from LN, we generated CAP-100, an antibody that specifically binds to hCCR7 and neutralizes its ligand-binding site and signaling. In various in vitro and in vivo preclinical models CAP-100 strongly inhibited CCR7-induced migration, extravasation, homing, and survival in CLL samples. Moreover, it triggered potent tumor cell killing, mediated by host immune mechanisms, and was effective in xenograft models of high-risk disease. Additionally, CAP-100 showed a favorable toxicity profile on relevant hematopoietic subsets. Our results validated CAP-100 as a novel therapeutic tool to prevent the access of CLL cells, and other neoplasia with nodal-dependence, into the LN niches, thus hitting a central hub in the pathogenesis of cancer. The first-in-human clinical trial (NCT04704323), which will evaluate this novel therapeutic approach in CLL patients, is pending.